Security and tourism in European cities - the multiple case study - Mekinc, Janez (Lex localis, 2017)
The purpose is to present current security and tourism issues in selected cities in Europe. The aim of the research is to present several approaches that cities have adopted in order to secure tourists. Research is designed as multiple case studies research design. Seven cities (Alba, Barcelona, Brasov, München, Rome, Saint-Denis and Brussel) are described regarding their security policies and safety, and findings of cross-case analysis are presented. . Four themes emerged from cross-case analysis: Security, tourism policy and citizens; Image, communication and public spaces; Managing the security of large events and Managing nightlife in the city. The findings show that cities use different policies, management, methods and practices to challenge security issues in tourism.
Keywords: civil protection; civilna zaščita; razvoj varnosti; security development; security planning; tourism; turizem; urban security; urbana varnost; varnostno načrtovanje